Differential action of medically important Indian BIG FOUR snake venoms on rodent blood coagulation. (February 2016) - Hiremath, Vilas; Nanjaraj Urs, A.N.; Joshi, Vikram; Suvilesh, K.N.; Savitha, M.N.; Urs. Amog, Prathap; Rudresha, G.V.; Yariswamy, M.; Vishwanath, B.S.
Abstract: Snakebite is a global health problem affecting millions of people. According to WHO, India has the highest mortality and/or morbidity due to snakebite. In spite of commendable research on Indian BIG FOUR venomous species; Naja naja and Bungarus caeruleus (elapid); Daboia russelii and Echis carinatus (viperid), no significant progress has been achieved in terms of diagnosis and management of biting species with appropriate anti-snake venom. Major hurdle is identification of offending species. Present study aims at differentiation of Indian BIG FOUR snake venoms based on their distinguish action on rodent blood coagulation. Assessment of coagulation alterations by elapid venoms showed negligible effect on re-calcification time, prothrombin time, activated partial thromboplastin time and factors assay (I, II, V, VIII and X) both in vitro and in vivo . However, viperid venoms demonstrated significant anticoagulant status due to their remarkable fibrinogen degradation potentials as supported by fibrinogenolytic activity, fibrinogen zymography and rotational thromboelastometry. Though results provide hint on probable alterations of Indian BIG FOUR snake venoms on blood coagulation, the study however needs validation from human victim's samples to ascertain its reliability for identification of biting snake species. Highlights: Indian BIG FOUR snake venoms exhibited differential action towards rodent blood coagulation. Viperid but not elapid venoms altered both intrinsic and extrinsic pathways of rodent blood coagulation. Except fibrinogen none of the common pathway factors of rodent blood were degraded by BIG FOUR venoms. Fibrinogen degradation by viperid venoms was supported by Rotational thromboelastometry